2022
DOI: 10.3389/fcvm.2022.897946
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after right ventricular outflow tract reconstruction with valve substitutes: A systematic review and meta-analysis

Abstract: IntroductionThis study aims to provide an overview of outcomes after right ventricular outflow tract (RVOT) reconstruction using different valve substitutes in different age groups for different indications.MethodsThe literature was systematically searched for articles published between January 2000 and June 2021 reporting on clinical and/or echocardiographic outcomes after RVOT reconstruction with valve substitutes. A random-effects meta-analysis was conducted for outcomes, and time-related outcomes were visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Our results did not demonstrate TA to be a potential risk factor for conduit dysfunction, reintervention-free survival, and overall survival. We believed that the reason behind this was that patients with TA generally underwent surgical conduit placement much earlier in life, in which PVOD had not yet developed 15,16 . Also, we had very limited number of TA patients in our cohort, which might not be enough to be statistically signi cant.…”
Section: Discussionmentioning
confidence: 99%
“…Our results did not demonstrate TA to be a potential risk factor for conduit dysfunction, reintervention-free survival, and overall survival. We believed that the reason behind this was that patients with TA generally underwent surgical conduit placement much earlier in life, in which PVOD had not yet developed 15,16 . Also, we had very limited number of TA patients in our cohort, which might not be enough to be statistically signi cant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, irreversible myocardial damage may occur ( 4 ). Although valved conduits have a good closure function, they have no growth potential and are associated with high reoperation rate; thus, they are not suitable for children ( 5 , 6 ). It has been widely recognized that autologous tissues should be spared as much as possible to avoid RVOT stenosis ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…No commercially available PPVRs are ideal and RVOT reconstruction will often require repeat operations later in life to replace dysfunctional prosthetics 18,19 . Importantly, freedom from RVOT reoperation varies depending on the clinical context, influenced by factors such as CHD etiology, age at implantation and PPVR type, as well as institutional and patient preferences.…”
Section: Reoperation Requirementsmentioning
confidence: 99%
“…A recent systematic review identified the primary indications for intervention due to right heart CHDs as Tetralogy of Fallot and truncus arteriosus, and left heart CHDs commonly required right heart intervention due to the use of the PV as an autograft in the Ross procedure 19 . PPVR implantation for truncus arteriosus tended to occur earlier in life (median age of 2.5 months), with a 10‐year freedom from reoperation of around 25% 19 .…”
Section: Reoperation Requirementsmentioning
confidence: 99%
See 1 more Smart Citation